Updating Standard Operating Procedures : Tuntutan Manajemen? Studi Kasus Pada Unit Gizi Rumah Sakit X Di Surabaya - Lidya Ratnasari Tejosaputra; Hendra Wijaya (InFestasi, 2018)
The purpose of this study is to analyze and evaluate the implementation of standard operational procedures (SOPs) in nutrition unit of X hospital in Surabaya after the change of management. The scope of the study is the implementation of SOPs that focused on the organizing of processing food in hospital’s kitchen. The study uses explanative qualitative approach with case study method. The types and sources of data are qualitative and primary data. Methods of data collection are interview, observation, and documentation.The results of the study show that the change of management caused many changes and adjustments in day to day operational implementation, but there is not enough updating the SOPs. The evaluation of SOPs reveals that the report needed by new management is not available as there are not enough documents in the existing SOPs to support the availability of the report. Hence, the updating of SOPs is necessary to fulfill the management demand.